The development of storytelling in two languages with words and gestures. (February 2015) - Laurent, Angélique; Nicoladis, Elena; Marentette, Paula
This was a cross-sectional study of storytelling development in French–English bilinguals between four and 10 years in both languages. Measures of both spoken and gestural use were examined as a function of age. The results showed that the children's spoken narrative abilities were related to age in both languages while their rates of gestures were not. The relationship between gesture use and narrative abilities was, at best, weak. These results suggest that fluent bilinguals develop narrative abilities in both languages simultaneously. We discussed the results of the present study in the light of ongoing research on the developmental relationship between speech and gesture in childhood.